Characteristics of rheumatoid arthritis patients at first presentation to a specialized rheumatology department - Vij, Amarjit Singh; Malaviya, Anand N.; Kumar, Sharath (International Journal of Research in Medical Sciences, 2017)
Background: Rheumatoid arthritis (RA) is a chronic, progressive, debilitating, systemic, autoimmune disease that mainly affects the diarthrodial joints. It is the most common form of inflammatory arthritis that occurs in approximately 1% of adults. The main objective is to study the characteristics of patients with Rheumatoid Arthritis (RA) at first presentation to a specialized rheumatology department. Methods: The study included 122 consecutive patients with RA, fulfilling 1987 American College of Rheumatology (ACR) criteria for RA at ‘Joint Disease Clinic’ of rheumatology department, at ISIC, New Delhi. Results: The mean age was 45.3 ± 12.4 years, F:M ratio, 8.4:1; maximum patients (31.1%) belonging to age group 30-40 years. Mean age at onset of symptoms was 38.1 ± 12.9 years and disease duration mode 5 years. 88% patients were literate and 59% referred by other patients. 14.8% patients had family history of RA, 7.38% (all males) were smokers. 16.4% female patients developed symptoms of arthritis within one year after delivery. 44.3% patients had severe, 50.8% moderate, 3.3% mild and 1.6% inactive disease (DAS 28[ESR] scoring system). 28.7% patients were taking treatment from alternative systems, 25.4% from orthopaedicians, 15.6% from internists and 8.2% from rheumatologists. Methotrexate and glucocorticoids were the most prescribed drugs (50.8% each) but in inappropriate doses. 23.8% patients had co-morbidities, hypothyroidism (9%) being the commonest. Conclusions: RA affects middle aged women. Hypothyroidism is the mostly associated autoimmune disease. The majority receive suboptimal / inappropriate treatment before visiting a rheumatologist. Most patients consult a rheumatologist at late stage in the disease often with deformities. Hence, increased awareness is needed about this disease among patients and doctors so that patients get timely referral to a rheumatologist for the proper management of this disease.